APLIKASI EKOENZIM PADA TANAMAN BUAH NAGA (Hylocereus undatus) UNTUK MENGENDALIKAN HAMA SEMUT API (Solenopsis invicta) - SUSLINGSIH, SRI ELSA; RAHMAN, ABDUL; YUSWANA, AGUNG; RAHAYU M, RAHAYU; HISEIN, WAODE SITI ANIMA; PAKKI, TERRY; HASAN, ASMAR; BOTEK, MUHAMMAD (Jurnal Agroteknos, 2022)
Dragon fruit (Hylocereus undatus) is one type of cactus plant that has favorable prospects to be developed economically and in accordance with tropical climates such as Indonesia. This plant does not escape from the disturbance of pests and plant disease organisms. The fire ant (Solenopsis invicta) is one of pests that cause damage during flowering and fruiting. This study aims to determine the concentration of an effective eco-enzyme solution to control fire ant pests on dragon fruit plants. This study used a completely randomized design consisting of three treatments, namely the concentration of the eco-enzyme solution 0 mL/L water (P0), the eco-enzyme solution concentration 0.5 mL/L water (P1) and the concentration of the eco-enzyme solution 1 mL/L water (P2). The variables observed were mortality and intensity of fire ant attacks on dragon fruit plants every day after application for seven days. The results showed that eco-enzyme solution concentration of 0.5 mL/L water was effective in killing fire ant pests and reducing the intensity of fire ant damage on dragon fruit plants.